Experimental investigation of turbulence modification in bubbly axisymmetric jets; Journal of Engineering Physics and Thermophysics; Vol. 24, iss. 2 - Alekseenko S. V. Sergey Vladimirovich; Dulin V. M.; Markovich D. M. Dmitry Markovich; Pervunin K. S. (2015, 2015)
Title screen